“Just War” — political fiction or credible postulate? - Bartula, Piotr (Folia Philosophica, 2017)
As the well-known proverb goes, war is a continuation of politics by other means. Every realistic political perspective acknowledges the possibility of war as the last resort in solving agonal conflicts. As such, politics is to war as the threat of force is to its actual use. With skepticism, my paper explores the presupposition that war can be a lawful, legitimate instrument of politics. Specifically, I consider two opposing “just war” paradigms- the realistic and moralistic.